Analysis of the Alignment of Bank NTB Syariah's Core Values 'AMANAH' with the Principles of Maqashid Syariah - Abdul Hafith; Abdul Malik; Baiq El Badriati; Muhammad Harfin Zuhdi (Lembaga Bale Literasi, 2025)
This study aims to reinterpret the value of trust in Islamic banking through the perspective of maqashid al-sharia with a case study on Bank NTB Syariah. The method used is a qualitative approach with a descriptive-analytical design and interpretive paradigm, through the analysis of internal documents and relevant scientific literature. The results of the study show that trust is not only understood as trust in transactions, but as a holistic principle that includes moral, social, and spiritual responsibility in all banking activities. The implementation of trust has been reflected in various aspects of the organization such as governance, service, human resource management, and supervisory systems. However, there is still a gap between normative values and empirical reality that shows that the internalization of trust has not been fully consistent in organizational practices. This condition emphasizes the need to strengthen a value-based work culture and an institutional system that is able to bridge the gap between ideal values and real implementation. As the main contribution, this study offers an integrative model of trust as a sustainability strategy for Islamic banking that connects the spirituality, governance, social, and economic dimensions. This model is believed to be able to strengthen public trust, increase competitiveness, and maintain institutional sustainability in the long term. Therefore, leadership with integrity, strengthening organizational culture, and ethics-based evaluation systems are key factors in ensuring that trust is consistently internalized and has a real impact on the institution's performance and reputation.